Impact of reach height on estimated rotator cuff compression risk in manual wheelchair users with spinal cord injury - Schaffer, K. M.; Madansingh, S. I.; Fortune, E.; Morrow, M. M.; Zhao, K. D.; Cloud-Biebl, B. A. (Journal of Applied Biomechanics, 2025)
Reaching is a common daily activity requiring a range of humeral elevation that contributes to rotator cuff compression. The purpose of this study was to estimate supraspinatus and infraspinatus tendon compression risk relative to the acromion and coracoacromial ligament during reaching by manual wheelchair users with spinal cord injury. A cross-sectional design was used to evaluate 8 participants (7 males, median [range] age 36 y [23-61]). Electromagnetic motion capture recorded shoulder kinematics while participants reached for a can at 2 heights: low (0.91 m) and high (1.37 m). Using 1 set of computed tomographic-based bone models and individual glenohumeral kinematics, compression risk was evaluated as the percentage of the reach activity and number of seconds that tendon insertions were less than 5 mm from scapular landmarks. Reach conditions were compared using a Wilcoxon signed-rank test (a = .05). Although not statistically significant, the supraspinatus and infraspinatus relative to the acromion had approximately 40% of the activity duration or 0.8 seconds more time under 5 mm in low versus high reach, indicating increased risk of compression. Compression risk estimates were consistent with prior publications on planar arm movements. Estimating the risk of tendon compression using absolute time may help with understanding cumulative exposure during day-to-day activity.